FEATURES OF EVALUATING THE EFFECTIVENESS OF ACTIVITIES AT THE BUKHARA STATE UNIVERSITY - Shodiev Alisher Khudoynazarovich (Galaxy International Interdisciplinary Research Journal, 2022)
This article presents an analysis of practical data on the features of evaluating the effectiveness of the Bukhara State University.